2012
DOI: 10.1111/j.1464-410x.2012.11340.x
|View full text |Cite
|
Sign up to set email alerts
|

Short (≤1 mm) positive surgical margin and risk of biochemical recurrence after radical prostatectomy

Abstract: What's known on the subject? and What does the study add? It has been suggested that a very short positive margin does not confer additional risk of BCR after radical prostatectomy. This study shows that even very short PSM is associated with increased risk of BCR. Objective To re‐evaluate, in a larger cohort with longer follow‐up, our previously reported finding that a positive surgical margin (PSM) ≤1 mm may not confer an additional risk for biochemical recurrence (BCR) compared with a negative surgical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…The importance of PSM has already been confirmed in recent studies, which have associated PSM characteristics, such as number and length of PSM and Gleason score at the margin site, to a higher risk of biochemical recurrence [65][66][67]. From this point of view, the possibility to predict presence of specimen-confined disease (SCD) (pT2-3a, R0, N0) could help clinicians to select patients who might benefit from radical prostatectomy monotherapy.…”
Section: Novel Patient Selection Tools For Surgery In High-risk Prostmentioning
confidence: 90%
“…The importance of PSM has already been confirmed in recent studies, which have associated PSM characteristics, such as number and length of PSM and Gleason score at the margin site, to a higher risk of biochemical recurrence [65][66][67]. From this point of view, the possibility to predict presence of specimen-confined disease (SCD) (pT2-3a, R0, N0) could help clinicians to select patients who might benefit from radical prostatectomy monotherapy.…”
Section: Novel Patient Selection Tools For Surgery In High-risk Prostmentioning
confidence: 90%
“…Traditionally considered as a tumor that develops over the long term, its high and very high-risk variants have been shown to behave in a very variable manner [3,4], with an irregular prognosis, which normally leads to the need for a multiple treatment approach to achieve appropriate cancer control [5,6]. This situation has spawned numerous works attempting to analyse the different preoperative (PSA, digital rectal examination, age, prostate Gleason score, uni/bilateral tumor involvement, percentage of affected cylinder, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective study by eastham et al examining the outcome of 2442 RPs, isolated posterolateral and posterior PSMs were an independent risk factor (HR 2.8, 95% CI 1.8-4.4 and HR 2.0 (95% CI 1.1-3.6, respectively)) for BCR compared to negative margins whereas other margin sites were not independently associated with BCR in their cohort. [50][51][52] Furthermore, the difference in the risk of BCR between close margins and PSMs was insignificant in the study by Izard et al 51 The proposed mechanism for close margins is that with additional sampling levels, a close margin may actually be positive. While some studies have reported higher risk of biochemical recurrence 43-45 others have not.…”
Section: Association Of Psms and Clinical Outcomesmentioning
confidence: 96%